Molecular Dynamics Assessment of Doxorubicin–Carbon Nanotubes Molecular Interactions for the Design of Drug Delivery Systems - Rozas-Soto, R; Contreras-Fuentes, M; Torres-Villanueva, C (Springer New York LLC, 2019)
Carbon nanotubes (CNTs) constitute an interesting material for nanomedicine applications because of their unique properties, especially their ability to penetrate membranes, to transport drugs specifically and to be easily functionalized. In this work, the energies of the intermolecular interactions of single-walled CNTs and the anticancer drug doxorubicin (DOX) were determined using the AMBER 12 molecular dynamics MM/PBSA and MM/GBSA methods with the aim of better understanding how the structural parameters of the nanotube can improve the interactions with the drug and to determine which structural parameters are more important for increasing the stability of the complexes formed between the CNTs and DOX. The armchair, zigzag, and chiral nanotubes were finite hydrogen-terminated open tubes, and the DOX was encapsulated inside the tube or adsorbed on the nanotube surface. Pentagon/heptagon bumpy defects and polyethylene glycol (PEG) nanotube functionalization were also studied. The best interaction occurred when the drug was located inside the cavity of the nanotube. Armchair and zigzag nanotubes doped with nitrogen, favored interaction with the drug, whereas chiral nanotubes exhibited better drug interactions when having bumpy defects. The π-π stacking and N-H…π electrostatic interactions were important components of the attractive drug-nanotube forces, enabling significant flattening of the nanotube to favor a dual strong interaction with the encapsulated drug, with DOX–CNT equilibrium distances of 3.1–3.9 Å. These results can contribute to the modeling of new drug-nanotube delivery systems. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.